What is American poetry? - Rahmatova Mehriniso Muhsinovna; Ganiyeva Nozanin Gayratovna (Genius Publishing Group, 2022)
This in the article initial class students in teaching interactive modern methods and them lesson in the process of application advantages about thought considerations is reported
Keywords: Native American; colonist; poetry; war